Lingguizhugan decoction alleviates obesity in rats on a high-fat diet through the regulation of lipid metabolism and intestinal microbiota - Huang, Wenjing; Wang, Jiuyuan; Xiao, Zixuan; Lin, Jiayi; Tan, Zhoujin; Sun, Guixiang (Frontiers in Microbiology, 2024)
BackgroundIndividuals with obesity often experience elevated blood lipid levels, leading to a chronic low-grade inflammatory state, exacerbating liver oxidative stress, and increasing the risk of various metabolic diseases. Recent evidence suggests that intestinal microbiota and short-chain fatty acids (SCFAs) play crucial roles in the development and progression of obesity. While the mechanisms by which Lingguizhugan decoction (LGZGD) intervenes in obesity by improving lipid metabolism, enhancing insulin sensitivity, and reducing inflammatory responses are well-documented, its potential in intestinal microbiota and SCFAs remains unclear. This study aims to explore the impact of LGZGD on high-fat diet (HFD) induced obesity in rats and its regulatory effects on intestinal microbiota and SCFAs, providing new insights for obesity prevention and treatment.MethodsFifty-one male SD rats were randomly divided into groups, with six in the normal control group (NC) receiving a ddH2O treatment and a standard diet. The remaining 45 rats were fed a high-fat diet (HFD) using D12451 feed. After 10 weeks, the rats on the HFD gained 20% more weight than the NC group, confirming the successful modeling of obesity. These rats were then randomly divided into the following groups: ddH2O high-fat diet model group (MC), 20 mg/kg/day Orlistat positive control group (Orlistat), 1.62 g/kg/day low-dose LGZGD group (LGZGL), and 3.24 g/kg/day high-dose LGZGD group (LGZGH) for 8 weeks. We evaluated changes in body weight, serum total cholesterol (TC), total triacylglycerol (TG), low-density lipoprotein cholesterol (LDL), and high-density lipoprotein cholesterol (HDL) levels. Fat and liver tissues were collected for pathological analysis. Intestinal contents were aseptically collected for 16S rRNA gene sequencing and gas chromatography–mass spectrometry (GC–MS) to assess gut microbiota and SCFA levels.ResultsLGZGD reduces body weight, TC, TG, LDL, and HDL levels, significantly reducing hepatic steatosis. Besides, it restored the richness and diversity of gut microbiota, which was reduced by HFD, altering the overall structure. Specifically, LGZGD significantly promoted the growth of Muribaculaceae and Dubosiella while inhibiting the growth of Christensenellaceae_R_7_group and UCG_005. It also restricts the production of caproic acid. Correlation analysis indicated positive correlations: Muribaculaceae with Butyric acid and Isovaleric acid; UCG_005 with TC, LDL, and HDL; and Christensenellaceae_R_7_group with TC and LDL.ConclusionLGZGD increased the abundance of beneficial gut microbiota in HFD-induced obese rats, improved gut microbiota dysbiosis, and inhibited the increase in caproic acid content. These results suggest that LGZGD can mitigate HFD-induced obesity, and its active components warrant further investigation.